Fishing for function – distinct roles of Bace1 and Bace2 in Zebrafish development. (25th March 2013) - Walter, Jochen
Abstract : Read the full article ' Loss of Bace2 in zebrafish affects melanocyte migration and is distinct from Bace1 knock out phenotypes ' on doi:10.1111/jnc.12198 .